SUCESSFULL MANAGEMENT OF CHILDHOOD BASIC-TYPE ESOTROPIA IN ADULT PATIENT: Poster Presentation - Case Report - Resident - VITRIANA, ANISA; M., Feti Karfiati; Caesarya, Sesy; Amiruddin, Primawita O.; Kuntorini, Mayasari Wahyu; Irfani, Irawati (Majalah Oftalmologi Indonesia, 2023)
Introduction : Strabismus in adults may indicate other pathological causes, such as neurological disorders or trauma. Diagnosis of esotropia in adult patients has to be made carefully to determine the right treatment. Management’s goal of strabismus in adult patients is mainly cosmetic by diminishing deviation. Case Illustration : A 46-year-old woman, complaint of inward deviation of both eyes since childhood. There were no complaints of double vision, headaches, nor trauma history. Visual acuity of right eye was 0.4 with BCVA and left eye was 0.8 with BCVA 0.8. Hirschberg test was 45o (Figure 2A). Prism cover test was 75 PD base out in near and distance. Patient was diagnosed with basic-type esotropia. The patient already given spectacles but the deviation persisted so she underwent bilateral medial rectus recess surgery (Figure 2B). Ocular alignment without spectacles 1 week after surgery showed orthotropia and small esophoria. (Figure 2C). Discussion : Each esotropia types has a different treatment approach. Basic-type esotropia with large deviation usually needs surgical treatment. Management of childhood onset strabismus in adult patients is challenging because those patients have lesser ability to maintain fusion. Older patients and large deviation are poor prognostic factors to achieve good functional and cosmetics outcome after strabismus surgery. Conclusion : Establishing a definite diagnosis in adult strabismus patients, including esotropia, is challenging. Careful diagnosis and management decision will determine the outcome of the patient’s condition.